Katelyn Woodhams: capstone - Woodhams, Katelyn, artist (Colorado State University. Libraries, 2013)
The artist's statement: In my work I like to explore new techniques in graphic design that combine my knowledge from my life as an artist and use those techniques to come up with something new and innovative. I love to design in illustrator, making vector illustrations and design elements as well as hand done typography. My style usually develops from something intricate and complicated and simplifies down to the final piece. I incorporate colors into every design I can, attempting to always create harmony and a specific feel for the piece. I intend to continue my career in graphic design working for a design firm or company that focuses on branding and identity.
Capstone contains the artist's statement, a list of works, and images of works.
Colorado State University Art Department capstone project.